Plasma D-Dimer Level Correlates with Age, Metastasis, Recurrence, Tumor-Node-Metastasis Classification (TNM), and Treatment of Non-Small-Cell Lung Cancer (NSCLC) Patients. (19th October 2021) - Guo, Jiqiang; Gao, Ying; Gong, Zhihua; Dong, Pengfei; Mao, Yajie; Li, Fang; Rong, Jianrong; Zhang, Junping; Zhou, Yongnian; Feng, Huijing; Guo, Hongxia; Gu, Linxia; et al.
Abstract : Objective . This study is aimed at teasing out the correlation of plasma D-dimer (D-D) levels to age, metastasis, TNM stage (tumor-node-metastasis classification), and treatment in non-small-cell lung cancer (NSCLC) patients of different ages, to facilitate early diagnosis of hypercoagulable state, choose appropriate treatment, and use appropriate anticoagulants. Hence, thrombosis and complications caused by excessive anticoagulants can be prevented; thrombus or disseminated intravascular coagulation (DIC) and other complications in elderly patients with NSCLC can be reduced or avoided. By monitoring the level of plasma D-D in patients with NSCLC, recurrence and metastasis can be predicted in the early stage and the TNM stage can be evaluated. Methods . A total of 670 patients with NSCLC were selected in Shanxi Bethune Hospital from March 2014 to October 2020 as the experimental group, and 950 healthy people were selected from the physical examination center of the same hospital as the control group. The data of patients with NSCLC diagnosed for the first time without any treatment were collected and grouped based on metastasis, TNM stage, treatment, and pathological type, and the correlation with plasma D-D level was analyzed. Plasma D-D levels were measured by immunoturbidimetry on an ACL TOP 700 Automatic Coagulation Analyzer. The patients were further divided into two groups according to different treatment methods, and the differences in plasma D-D levels between patients receiving chemotherapy and those receiving targeted therapy in different treatment cycles were analyzed. The correlation between D-D levels and age in healthy controls was analyzed. The difference in D-D levels between NSCLC patients and healthy controls of the same age was analyzed. Results . All data of both the experimental group and the control group were normally distributed. The average age of the experimental group was 61.31 ± 6.23 (range: 36-92) years. The average age of the control group was 61.14 ± 11.12 (range: 35-85) years. There was no significant difference in gender between the experimental group and the control group (p > 0.05 ). The plasma D-D level of NSCLC patients was significantly higher than that of the healthy controls (p < 0.05 ). No significant difference in plasma D-D level was found between NSCLC patients of different genders, and the finding was similar between healthy controls of different genders (p > 0.05 ). Significant difference in the D-D level was found between the groups of 30-59 years and 60-69 years (p < 0.05 ), between groups of 60-69 years and 70-79 years (p < 0.05 ), and between 70-79 years and ≥80 years (p < 0.05 ). The plasma D-D level of patients ≤ 79 years old increased with age, but it decreased in those over 80 years old. According to Pearson correlation analysis, there was a positive correlation between the D-D level and the age of NSCLC patients under 79 years old (p < 0.05 ). The differences in D-D levels between the four age groups were statistically significant (p < 0.05 ), showing an upward trend of the D-D level in healthy controls with the increase of age. There were statistically significant differences in D-D levels between NSCLC patients and healthy controls of the matching age group (p < 0.05 ), suggesting that NSCLC patients had significantly higher D-D levels than healthy people of the same age group. The differences in D-D levels between NSCLC patients without metastasis, NSCLC patients with metastasis, and healthy people were statistically significant (p < 0.05 ). The patients with metastasis had the highest D-D level, and healthy people had the lowest D-D level. The difference in plasma D-D levels between patients of different TNM stages was statistically significant (p < 0.05 ). Patients with an advanced TNM stage tended to have higher D-D levels. The TNM stage and D-D level of NSCLC patients changed significantly before and after treatment. An earlier stage was related to a more obvious change in D-D levels after treatment with a statistically significant difference (p < 0.05 ). A more advanced stage was associated with a smaller change in the D-D level after treatment, with no statistically significant difference (p > 0.05 ). The plasma D-D levels before and after four cycles of chemotherapy or targeted therapy were higher than those of the healthy control group, and the differences were statistically significant (p < 0.05 ). The D-D level of patients after chemotherapy was significantly lower than that before chemotherapy (p < 0.05 ), but there was no significant difference before and after targeted therapy (p > 0.05 ). The D-D level after the first cycle of chemotherapy was higher than that before chemotherapy. The level of D-D after the third and fourth cycles was significantly lower than that before chemotherapy (p < 0.05 ). No significant difference was found between the D-D level before treatment and that after four cycles of chemotherapy (p > 0.05 ). Conclusion . It is suggested that coagulation test indexes should be included to evaluate the treatment regimen for NSCLC patients. Most patients with NSCLC are in a hypercoagulable state, which is related to age, tumor invasion and metastasis, recurrence, and treatment. Regular monitoring of plasma D-D levels can facilitate early diagnosis of a hypercoagulable state and timely and appropriate use of anticoagulants, to avoid or reduce complications such as venous thromboembolism in NSCLC patients and to prevent the risk of bleeding caused by excessive anticoagulants. Clinicians can choose the treatment with less harm and maximum benefit for NSCLC patients based on the plasma D-D level. When in a hypercoagulable state, the body's blood viscosity increases, making it more conducive to the growth and infiltration of tumor cells. Our study shows that the recurrence and metastasis of NSCLC are related to coagulation indexes, which provides a theoretical basis for the early diagnosis and treatment of recurrent and metastatic NSCLC.